2021
DOI: 10.1159/000517949
|View full text |Cite
|
Sign up to set email alerts
|

Drain Amylase Levels in the Early Diagnosis of Gastric Leak after Laparoscopic Sleeve Gastrectomy

Abstract: Highlights of the Study• Gastric leak is the most dreaded septic complication after sleeve gastrectomy.• With the advent of enhanced recovery after surgery (ERAS) protocols, the early detection of gastric leak following laparoscopic sleeve gastrectomy (LSG) is imperative. • The use of drain amylase levels to detect enteric or pancreatic leak has been described previously.• In this study, we have investigated the relationship between this index and the appearance of a gastric leak after LSG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…High drain fluid amylase level rates might be seen in all leaks in the gastrointestinal system, especially in pancreatic fistula (15). However, in another study; the determination of drain fluid amylase levels after sleeve gastrectomy was shown as a significant indicator of gastric leak with high sensitivity and specificity (16).…”
Section: Discussionmentioning
confidence: 94%
“…High drain fluid amylase level rates might be seen in all leaks in the gastrointestinal system, especially in pancreatic fistula (15). However, in another study; the determination of drain fluid amylase levels after sleeve gastrectomy was shown as a significant indicator of gastric leak with high sensitivity and specificity (16).…”
Section: Discussionmentioning
confidence: 94%
“…a) Extravasation of contrast dye or GIT discharges through the intraperitoneal drain (The drain amylase levels after LSG is a significant predictive factor of GSLL with high specificity and sensitivity) (16) . b) Confirmatory laboratory and clinical evidence of sepsis.…”
Section: Definition and Classification Of Gsllmentioning
confidence: 99%